Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak UMKM Pada KPP Pratama Praya Kabupaten Lombok Tengah - Sri Wulandari; Endang Kartini (Akuntabel: Jurnal Ilmiah Akuntansi, 2024)
This study aims to empirically examine the effect of tax knowledge, tax socialization, tax service quality, tax sanctions on MSME taxpayer compliance at KPP Pratama Praya, Central Lombok Regency. This research is a type of quantitative research with an associative approach. The population in this study is MSME taxpayers who are registered at KPP Pratama Praya, Central Lombok Regency. The sample in this study amounted to 100 respondents. Data collection techniques in this study were carried out by distributing questionnaires directly to research respondents. The analytical method used in this study is multiple linear regression using the SPSS software program version 25. The results of this study indicate that the independent variable of tax knowledge does not have a significant effect on MSME taxpayer compliance. The tax socialization variable has a significant effect on MSME taxpayer compliance. The variable quality of taxation services has a significant effect on MSME taxpayer compliance, and the variable taxation sanctions has a significant effect on MSME taxpayer compliance. The independent variable is able to influence the dependent variable (MSME taxpayer compliance) by 82%. While the remaining 18% is influenced by other variables outside this research model.